1997
DOI: 10.1530/eje.0.1370146
|View full text |Cite
|
Sign up to set email alerts
|

The effects of two doses of replacement growth hormone on the biochemical, body composition and psychological profiles of growth hormone-deficient adults

Abstract: This study examined the effects of growth hormone (GH) replacement on the insulin-like growth factor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…It is well documented that GHD has a negative impact on QoL in adults (8,30,31), and several studies have reported an improvement following GH treatment (32)(33)(34)(35); this has been reported to be paralleled by a reduction in healthcare consumption (34,35). The present data showed QoL to be equally impaired in the IGHD and the MPHD group at baseline; both groups responded favourably to 2 years of GH treatment.…”
Section: Discussionsupporting
confidence: 69%
“…It is well documented that GHD has a negative impact on QoL in adults (8,30,31), and several studies have reported an improvement following GH treatment (32)(33)(34)(35); this has been reported to be paralleled by a reduction in healthcare consumption (34,35). The present data showed QoL to be equally impaired in the IGHD and the MPHD group at baseline; both groups responded favourably to 2 years of GH treatment.…”
Section: Discussionsupporting
confidence: 69%
“…Indeed, a placebo effect on QoL has been observed using the Symptom Checklist-90 (SCL-90), the Social Adjustment Scale (SAS) (Florkowski et al 1998), the NHP (Burman et al 1995, Verhelst et al 1997, and the PGWB (Carroll et al 1997). Double-blind, placebo-controlled protocols have been developed to overcome the placebo effect, but the overt physical changes resulting from GH therapy render a true 'double-blind' protocol virtually impossible (Mardh et al 1994).…”
Section: Placebo Effectmentioning
confidence: 99%
“…One of the most important impairments from a patient's point of view is the decline in health-related quality of life (HRQoL). The HRQoL decay is perceived in the areas of energy, emotional reaction, social behaviour, general health, self-control, anxiety, vitality, mood and sense of well-being measured by Nottingham Health Profile and the Psychological General Well-Being Schedule (2). Most studies showed a benefit of GH replacement on HRQoL (1).…”
Section: Introductionmentioning
confidence: 99%